PCR based detection of fumonisin producing strains of Fusarium verticillioides and gene related to toxin production - Patharjan2, P. Karthikeyan3 , P. Saravanakumar4, M. Siva5, P.S. Aruna Bhavani5, P. Palani5, V. Karthikeyan1, R. Rajarajan1, S. (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-bidi-font-weight: bold; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Fusarium<span style="font-size: 8pt; font-family: Byington; mso-bidi-font-weight: bold; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> verticillioides produces Fumonisins are a group of mycotoxins that contaminate food and feed products posses maximum threat to human and animal health. In this work Eighty two strains of Fusarium species collected from infected rice samples were subjected to PCR assay to discriminate fumonisin producing and nonproducing strains with Inter Generic Spacer region (IGS) of rDNA coding units specific primer named as VERTF-1/VERTF-2 were used. 21 isolates of F. verticillioides scored positive for VERTF-1/ VERTF-2 pair of primers proves to be potential fumonisin production and 25 isolates were scored negative. Specific primers for polyketide synthase (PKS) gene FUM1-(previously FUM5) were used to all 83 strains resulted in positive signals observed in 21 strains of F. verticillioides. This present study proves the efficiency of IGS and gene specific primer also represents well for Fusarium strains isolated from rice also. For both primers PCR detection was consistent even at 100 pg/μl concentration of genomic DNA. This quite rapid and specific method helps in accurate discrimination of Fumonisin producing strains.